PENANGANAN PERUMAHAN TIDAK LAYAK HUNI DI WILAYAH PANTAI KABUPATEN KUTAI KARTANEGARA, KALIMANTAN TIMUR - Citra Anggita (INFO-TEKNIK, 2013)
Housing and residential construction is basically the duty and responsibility of the people themselves . In this case the government is obliged to provide facilities and create a climate that encourages the growth and development of initiatives and governmental organizations in order to foster the implementation and development can take place in an orderly manner . The purpose of this study provide policy inputs for handling housing in the Capital District Coastal Region in realizing housing livable and healthy , safe , harmonious , orderly and sustainable in Kabupaten Kutai Kartanegara. Location of the study in 6 ( six ) Capital District Coastal Region Kutai Kartanegara . Data analysis was performed by means of verbal ( qualitative ) . Based on the research results , it is necessary to repair efforts on facilities and infrastructure in coastal areas , the need for local governments to construct a scenario the development of housing and settlements in the area in the form of Housing Development Plan and Regional Development (RP4D ) and have institutional / agency that coordinates programs and activities and residential housing.